Binge Eating Disorder and Cognition (Research, Society and Development, 2020)
The objective was to investigate the relationship between Periodic Compulsive Eating Disorder (BED) and cognitive dysfunction among university students. To this end, a narrative review was carried out with articles from the Pubmed database, between 2010 and 2020; using as descriptors “binge eating disorder”, “adolescence”, “student”, “cognition” and “college”, in addition to AND as a Boolean operator. Based on the findings of these articles, it was found that there is a direct relationship between BED and the variables gender, sexuality, culture, beauty standards, cognition with rumination of ideas and affective aspects such as depression. Therefore, it can be concluded that culture can cause psychological distress and BED, with the influence of cognition and affective patterns.